2021
DOI: 10.1007/s41549-021-00057-3
|View full text |Cite
|
Sign up to set email alerts
|

The Time–Frequency Relationship between Oil Price, Stock Returns and Exchange Rate

Abstract: The concept of time scales is essential for modeling financial decisions. This paper investigates time-frequency relationships across time scales between stock market returns, crude oil prices and exchange rates by applying wavelet analysis technique over the period 1999 to 2021. We find evidence of several strong co-movements between oil price and stock market and between oil price and foreign exchange rate in India. Each of these associations is linked with some important macroeconomic events. This implies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…This study confirms the debilitating effects of oil price shock on exchange rate dynamics in Nigeria. Empirical studies that found the same results for net oil-exporting countries are Tian et al (2020), Nwosa (2020), Abdullah and Muhammad (2021); Igbinovia and Ogiemudia (2021); Li (2021); Touil and Merabet (2021); Das (2021) and Ajeigbe (2022). Interestingly, the effects of the monetary policy rate, trade balance and the price level on global oil price are negligible.…”
Section: Discussion Of Findingsmentioning
confidence: 75%
See 1 more Smart Citation
“…This study confirms the debilitating effects of oil price shock on exchange rate dynamics in Nigeria. Empirical studies that found the same results for net oil-exporting countries are Tian et al (2020), Nwosa (2020), Abdullah and Muhammad (2021); Igbinovia and Ogiemudia (2021); Li (2021); Touil and Merabet (2021); Das (2021) and Ajeigbe (2022). Interestingly, the effects of the monetary policy rate, trade balance and the price level on global oil price are negligible.…”
Section: Discussion Of Findingsmentioning
confidence: 75%
“…The empirical literature on the nexus between oil price dynamics and exchange rate behaviour is already proliferated with studies targeted at net oil exporters and net oil importers, while a few other studies combined panel of countries without recourse to the specificity of their trading status. The first category includes studies conducted by Abdullah and Muhammad (2021); Ajeigbe (2022); Das (2021); Igbinovia and Ogiemudia (2021); Li (2021); Nwosa (2020); Tian et al (2020); Touil and Merabet (2021); among others. For the second category, the studies of Baghestani and Toledo (2019); Vochozka et al (2020); Castro & Jimenez‐Rodrıguez, 2020; Allam et al 2020 are few of the recent studies while Baek (2020) combined a panel of net oil importers and net oil exporters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Barro et al (2020), Das (2021), Cauwenberge et al (2021) and Sim et al (2022 claimed that the growing volatility in the financial market around the world had been caused by the high level of uncertainty. Employing wavelet coherence and partial wavelet coherence model, Singh et al (2021) found the high degree of correlation between exchange rate movement and the pandemic in G7 countries during the period from January 4, 2021 to July 31, 2021.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mhd Ruslan and Mokhtar (2021) using a Garch model based on the daily data of the last four years, examined the effect of stock market fluctuations on shipping costs. Das (2021) explored the relationship between time series between oil price, stock returns, and exchange rate and used a 3-year period to conclude that oil price significantly impacted the Indian economy. Bashir et al (2021) investigated the macroeconomic sensitivity and its level of volatility by studying the New York Stock Exchange and using a Garch model to analyse an 18-year interval.…”
Section: Literature Reviewmentioning
confidence: 99%